Amorphous modified silyl-terminated 3D polymer electrolyte for high-performance lithium metal battery. (November 2017) - Lin, Zhiyuan; Guo, Xianwei; Yu, Haijun
Abstract: Polymer electrolyte has been considered to eliminate the safety issue that caused by the lithium dendrite growth in the liquid electrolyte for the high-energy lithium metal battery. However, the practical applications of polymer electrolyte are still impeded by the low Li ionic conductivity, weak interfacial compatibility, low thermal stability and narrow electrochemical window. In this study, we have proposed a novel modified silyl-terminated polyether based polymer electrolyte by a cross-linking fabrication method. With a three-dimensional network structure, the amorphous polymer electrolyte has high ionic conductivity ( 0.36 mS cm −1 ) at room temperature, much higher thermal stability (Tm = 379 °C), high lithium ion transference number ( 0.65), stable electrochemical window up to 5.0 V ( vs. Li + /Li) and an excellent compatibility to the electrode. With LiFePO4 cathode and this polymer electrolyte, the lithium metal battery delivers the high specific capacity of 130 mA h g −1 at 1 C rate over 300 cycles, and 105 mA h g −1 at 3 C rate with a superb cycling stability over 600 cycles at room temperature. We believe that this polymer electrolyte is a promising candidate for the practical applications and brings a new way to develop the high performance electrolyte for the lithium metal battery. Graphical abstract: Amorphous polymer electrolyte using a novel modified silyl-terminated polyether possess high ionic conductivity ( 0.36 mS cm −1 ) at room temperature, much higher thermal stability (Tm = 379 °C), high lithium ion transference number ( 0.65), stable electrochemical window up to 5.0 V ( vs. Li + /Li) and an excellent compatibility to the electrode. The lithium metal battery with developed polymer electrolyte present excellent electrochemical performance, showing strong potential for practical applications. Highlights: A novel cross-linked modified silyl-terminated polyether (MSTP)-PE for solid state battery was developed. This MSTP-PE has a high ionic conductivity (0.36 mS cm −1 ) at room temperature, much higher thermal stability (Tm = 379 °C), high lithium ion transference number (0.65), stable electrochemical window up to 5.0 V ( vs. Li + /Li) and a good compatibility to the electrodes. The lithium metal battery with a LiFePO4 cathode using MSTP-PE can deliver the high specific capacity of 130 mA h g −1 at 1 C rate over 300 cycles, and the specific capacity of 105 mA h g −1 at 3 C rate with an excellent cycling stability up to 600 cycles at room temperature.